Balancing the corrosion resistance and through-plane electrical conductivity of Cr coating via oxygen plasma treatment. (20th January 2021) - Wang, Xian-Zong; Fan, Hong-Qiang; Muneshwar, Triratna; Cadien, Ken; Luo, Jing-Li
Abstract: Developing an electrically conductive and corrosion-resistant coating is essential for metal bipolar plates of polymer electrolyte membrane fuel cells (PEMFCs). Although enhanced corrosion resistance was seen for Cr coated stainless steel (Cr/SS) bipolar plates, they experience a quick decrease of through-plane electrical conductivity due to the formation of a porous and low-conductive corrosion product layer at the plate surface, thus leading to an increase in interfacial contact resistance (ICR). To tackle this issue, the multilayer Cr coatings were deposited using the magnetron sputtering with a remote inductively coupled oxygen plasma (O-ICP) in the present study. After the O-ICP treatment, a Cr oxide layer (CrO*) is formed on the specimen surface. The CrO*/Cr/SS has a remarkably lower stable corrosion rate ( i ss ) than that of the native Cr oxides (CrOn /Cr/SS). Compared with CrOn /Cr/SS, the excellent performance of CrO*/Cr/SS is attributed to a denser and thicker surface layer of CrO* with Cr being oxidized to its highest valence state, Cr (VI). More importantly, the through-plane electrical conductivity of the specimens treated by the optimized O-ICP decreases much slowly than CrOn /Cr/SS and thus, the increament of ICR of CrO*/Cr/SS after the potentiostatic polarization test is considerably smaller than that of CrOn /Cr/SS, which is benefited from the reduced i ss that mitigates the deposition of corrosion products and hinders further oxidation of Cr coating. Therefore, CrO*/Cr/SS proves to be a well balanced trade-off between corrosion resistance and through-plane electrical conductivity. The results of this study demonstrate that O-ICP treatment on a conductive metal coating is an effective strategy to improve the corrosion resistance and suppress the increase of ICR over the long-term polarization. The technique reported herein exhibits its promising potential application in preparing corrosion resistant and electrically conductive coatings on metal bipolar plates to be used in PEMFCs.